2020
DOI: 10.1002/jpen.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Preoperative Home‐Delivered, Protein‐Rich Meal Service to Improve Protein Intake in Surgical Patients: A Randomized Controlled Trial

Abstract: Background The preoperative period likely provides an important opportunity to improve postoperative recovery, as suggested by the finding that low nutrition status is a predictor of increased postoperative complications and longer length of stay (LOS). It was investigated whether a home‐delivered, protein‐rich meal service improves protein intake relative to requirements within 3 weeks prior to surgery compared to usual care (UC). Methods This randomized controlled trial included adults (n = 126) with planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The repartition of surgical procedures in the 25 studies was as follows: abdominal (11/24, 639 patients), thoracic (3/24, 277 patients), urologic (4/24, 272 patients), vascular (2/24, 177 patients) and orthopaedic (2/24, 51 patients). Three studies included different types of surgery (654 patients) 44 , 61 , 64 . The case mix was as follows: abdominal and urologic (432 patients), neurosurgery and abdominal (96 patients), urologic, abdominal, gynaecological and orthopaedic (126 patients).…”
Section: Resultsmentioning
confidence: 99%
“…The repartition of surgical procedures in the 25 studies was as follows: abdominal (11/24, 639 patients), thoracic (3/24, 277 patients), urologic (4/24, 272 patients), vascular (2/24, 177 patients) and orthopaedic (2/24, 51 patients). Three studies included different types of surgery (654 patients) 44 , 61 , 64 . The case mix was as follows: abdominal and urologic (432 patients), neurosurgery and abdominal (96 patients), urologic, abdominal, gynaecological and orthopaedic (126 patients).…”
Section: Resultsmentioning
confidence: 99%
“…This was a post-hoc analysis of a randomized controlled trial (RCT), which was conducted at two hospitals in the Netherlands (ClinicalTrials.gov NCT03488511) [21]. The Medical Ethics Committee of the Radboudumc indicated that no formal approval was required for this study (2016-3043) (clinicaltrials.gov: NCT03488511).…”
Section: Study Population and Designmentioning
confidence: 99%
“…Participants received the high frequency protein-rich meal service at home in the pre-operative setting for three weeks. This meal service consisted of six small, protein-rich dishes per day, including a morning snack (shakes: 5-10 g protein), lunch (salads and soups: 7-25 g protein), afternoon snack (5-19 g protein), dinner (hot meal and dessert: 16-39 g protein) developed by Radboudumc and a caterer (Supplementary Table S1) [21]. Data on energy and protein content of the meals was provided in the original publication [21].…”
Section: Nutritional Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, research of meal delivery has generally been heterogenous in population, duration, and outcome, focusing predominantly on providing meals to vulnerable groups such as older adults ( 12 , 13 ), people experiencing food insecurity ( 14 ), those at risk for hospital readmissions or procedure complications ( 15 , 16 ), and those with multiple chronic conditions or complex comorbidities ( 17 , 18 ). Few research studies have explored meal delivery as a strategy for implementing healthy eating habits to improve outcomes for people with type 2 diabetes.…”
mentioning
confidence: 99%